CURRENT STATUS AND RESULTS OF PROFESSIONAL AND METHODOLOGICAL TRAINING OF PRE-SERVICE FRENCH TEACHERS AT UNIVERSITY LEVEL - Nataliia V. Maiier; Lesia V. Bondar (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article is devoted to the study of the current state and results of professional and methodological training of the pre-service French teachers. The pre-service French teachers get a higher education according to the educational program “Foreign languages and literatures, methods of teaching foreign languages and foreign literature (French and a second Western European language)” in the specialty 014 Secondary education, specialization 014.023 French language and literature for the first (bachelor) level of higher education. To achieve the goal of the research, qualitative and quantitative methods were used. The qualitative methods included an anonymous survey of students in order to find out their attitude to the organization of the educational process, to demonstrate how the students evaluate the acquired methodical knowledge and skills in the process of French teacher’s professional and methodical activity in general secondary education institutions, to show students’ attitude towards the organization of pedagogical practice in the French language in institutions of general secondary education, as well as the assessment by students of the level of acquired methodical skills for carrying out the professional and methodical activity of a French teacher and the assessment by the teacher according to established criteria. Cronbach’s alpha coefficient of reliability was used as a quantitative method to process the obtained results in order to determine the results of professional and methodological training and the professional and methodical competence formation of the pre-service French teachers. In the research, it was found that the professional and methodological training of the pre-service teachers of French as a foreign language lasts for four semesters. The professional and methodological training is carried out within the mandatory (curricular discipline “Methodology of teaching French in institutions of general secondary education” and practical training, which is implemented in two types of pedagogical practice) and optional disciplines. In order to expand the content of targeted training (in the period of 2021-2022 academic year), the preservice French teachers chose the following optional disciplines: “Testing in French language learning” and “Methodology for the formation of French-speaking linguistic and sociocultural competence”). Within the academic disciplines, the pre-service French teachers mastered methodical knowledge and skills of planning lessons by developing plans of the lessons’ parts and the whole French language lessons. They used various teaching aids, independently developed non-standardized tests for the formative assessment of the foreign language competence, and integrated linguistic and sociocultural competences. The preservice French teachers apply their knowledge and skills in the proposed conditions – training (during the educational pedagogical practice “Educational Studies (methodical aspect)”) and real (during the production pedagogical practice in an institution of general secondary education). In the process of professional and methodical training, current and summative types of assessment are applied. The criteria for control were established by the teacher. The results of the professional and methodological training of the pre-service French teachers during the educational process as well as the results of the exam and the results of their performance of tasks of various types of pedagogical practice were analyzed. The results were higher than 0.7 according to Cronbach’s alpha coefficient of reliability. This proves the sufficient level of formation of the professional and methodological competence of the pre-service French teachers under the specified educational program. On the basis of the conducted research, recommendations were formulated to increase the effectiveness of the professional and methodological training of the preservice French teachers: 1) widely use self-assessment and peer-assessment; 2) compare the students’ assessment with teachers; 3) analyze and interpret the obtained results; 4) systematically involve students in reflection, in particular methodical; 5) to involve the students in different types of pedagogical practice. It is promising to study the impact of the content and scope of professional and methodological training on the achievement of program learning outcomes within educational programs in the specialty 014 Secondary education for the training of the pre-service French teachers.